Magnetic reversal stratigraphy in theOligocene succession of the Ebro Basin, Northern Spain. - Friend, P.F.; Brazier, S.A.; Cabrera, L.; Shaw, J.; Feistner, K.W.A. (Cuadernos de Geología Ibérica, 1988)
Sin resumen